Enhanced bioremediation of 4-nonylphenol and cadmium co-contaminated sediment by composting with Phanerochaete chrysosporium inocula. (February 2018) - Xu, Piao; Lai, Cui; Zeng, Guangming; Huang, Danlian; Chen, Ming; Song, Biao; Peng, Xin; Wan, Jia; Hu, Liang; Duan, Abing; Tang, Wangwang
Graphical abstract: Highlights: P. chrysosporium inocula and proper C/N ratios accelerated the composting process. P. chrysosporium inocula promoted TOC loss, NP degradation and Cd passivation. LiP, MnP, CAT and PPO participated in organic chemical degradation. Microbial community structure variation contributed to chemical transformation. Depleted in bioavailability occurred in contaminated sediment via composting. Abstract: Composting is identified as an effective approach for solid waste disposal. The bioremediation of 4-nonylphenol (4NP) and cadmium (Cd) co-contaminated sediment was investigated by composting with Phanerochaete chrysosporium ( P. chrysosporium ) inocula. P. chrysosporium inocula and proper C/N ratios (25.51) accelerated the composting process accompanied with faster total organic carbon loss, 4NP degradation and Cd passivation. Microbiological analysis demonstrated that elevated activities of lignocellulolytic enzymes and sediment enzymes was conducive to organic chemical transformation. Bacterial community diversity results illustrated that Firmicutes and Proteobacteria were predominant species during the whole composting process. Aerobic cellulolytic bacteria and organic degrading species played significant roles. Toxicity characteristic leaching procedure (TCLP) extraction and germination indices results indicated the efficient detoxification of 4NP and Cd co-contaminated sediment after 120 days of composting. Overall, results demonstrated that P. chrysosporium enhanced composting was available for the bioremediation of 4NP and Cd co-contaminated sediment.